TATA KELOLA KEAMANAN INFORMASI LAYANAN TI MENGGUNAKAN FRAMEWORK ITIL V3 DOMAIN SERVICE DESIGN DI LINGKUNGAN SMKN 4 PADALARANG - Rinrin Risani Rahmawati; Yucki Prihadi (Scientia Regendi, 2021)
Information technology is now widely used for everyday purposes, ranging from administrative affairs of offices, hospitals to the service at the level of education. SMKN 4 Padalarang as an educational institution is expected to follow the development of information technology (IT) in order to support the process of learning and teaching activities and can build the quality of human resources. However, we still do not have an adequate IT governance and management until now. Especially which related to IT services and also faced with the limited problem of human resources where the field is not comparable with the number of IT service users, also the weak awareness of service users to the security factor. Implementation of Information Security Governance in educational institutions has an important role in the development and application of information technology (IT) they have. This research focuses on making Information Security Governance using ITIL V3 Domain Service Design framework so it can be a comprehensive procedure / policy and can be used in every educational institution especially in the plain of SMKN / SMA equal. The result of this design is Standard Operating Procedure (SOP) for IT services. We expect this research can help SMKN 4 Padalarang to improve its service capability and improve its security and role. Keywords: IT Services, ITIL V3, Service Design, Standard Operating Procedure.